Polishing pad and polishing device

The polishing pad with hollow particles having protrusions on their inner surfaces addresses the issue of coarse abrasive grain component formation, reducing scratches on polished objects and improving the CMP process.

JP2025056988APending Publication Date: 2025-04-09FUJIBO HLDG

Patent Information

Application Number
JP2023166569
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The formation of coarse abrasive grain components within the hollow particles on the polishing pad surface during chemical mechanical polishing (CMP) leads to scratches on the polished objects, such as semiconductor wafers.

Method used

A polishing pad with a polishing layer comprising a resin and hollow particles, where the hollow particles have one or more protrusions on their inner surface, reducing the accumulation and agglomeration of abrasive grain components.

Benefits of technology

The presence of protrusions on the inner surface of the hollow particles suppresses the formation of coarse abrasive grain components, thereby reducing scratches on the polished objects and enhancing the polishing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056988000001_ABST
    Figure 2025056988000001_ABST
Patent Text Reader

Abstract

To provide a polishing pad and a polishing device which suppress occurrence of a coarse abrasive grain component, and can reduce scratch in an object to be polished, when the object to be polished is polished.SOLUTION: A polishing pad 10 includes a polishing layer 11, wherein the polishing layer 11 contains a resin 111 and hollow particles 112 dispersed in the resin 111, and the hollow particles 112 have one or more projections 112C on an inner surface 112A of the hollow particles 112.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad and a polishing apparatus. [Background technology]

[0002] Conventionally, chemical mechanical polishing (CMP) using a slurry and a polishing pad has been used to polish objects such as semiconductor wafers because extremely precise flatness is required for such objects. CMP is a method in which a slurry is supplied to the polishing surface of a rotating polishing pad while pressing the object to be polished, such as a semiconductor wafer, against the polishing pad and rotating the pad to polish the surface of the object.

[0003] It is currently known that hollow particles are dispersed in the polishing layer constituting the polishing pad (see, for example, Patent Documents 1 and 2). In the polishing layer containing such hollow particles, the hollow particles are located on the surface of the polishing layer and open, so that the slurry can be held within the hollow particles, and therefore a large amount of slurry can be held on the surface of the polishing layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-322877 [Patent Document 2] JP 2010-274362 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, nano-sized abrasive grains contained in the slurry may accumulate and aggregate within hollow particles located on the surface of the polishing layer, forming coarse abrasive grains. When these coarse abrasive grains are exposed on the surface of the polishing layer as polishing proceeds, they may cause scratches on the workpiece.

[0006] The present invention has been made to solve the above problems, and aims to provide a polishing pad and a polishing apparatus that can suppress the generation of coarse abrasive grains during polishing of an object to be polished and reduce scratches on the object to be polished. [Means for solving the problem]

[0007] [1] A polishing pad having an abrasive layer, the abrasive layer comprising a resin and hollow particles dispersed in the resin, the hollow particles having one or more protrusions on their inner surfaces.

[0008] [2] The polishing pad according to [1] or [2] above, wherein the porosity of the hollow particles is 20% or more and 60% or less.

[0009] [3] The polishing pad according to [1] or [2] above, wherein the polishing layer has holes formed by openings of the hollow particles on the surface of the polishing layer, and the ratio of the height of the convex portion in the hole to the average opening diameter of the hole is 0.01 or more.

[0010] [4] The polishing pad according to any one of [1] to [3] above, wherein there are two or more convex portions for each hollow particle, and the gap between the convex portions is 5 μm or less.

[0011] [5] The polishing pad according to any one of [1] to [4] above, wherein the arithmetic mean roughness of the inner surface of the hollow particles is 0.1 μm or more.

[0012] [6] A polishing apparatus comprising the polishing pad described in any one of [1] to [5] above. Effect of the Invention

[0013] According to the present invention, it is possible to provide a polishing pad and a polishing apparatus capable of suppressing the generation of coarse abrasive grain components when polishing an object to be polished, thereby reducing scratches on the object to be polished. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic diagram of a polishing pad according to an embodiment. [Diagram 2] FIG. 2 is an enlarged view of a portion of FIG. [Diagram 3] FIG. 3 is an enlarged view of the hollow particle and its vicinity in FIG. [Figure 4] FIG. 4 is a schematic diagram of a polishing apparatus including a polishing pad according to an embodiment. [Diagram 5] FIG. 5 is an SEM image of a cross section of the polishing layer of the polishing pad according to Example 1 at a magnification of 10,000 times. [Figure 6] FIG. 6 is an SEM image at 1000 times magnification of the cross section of the polishing layer of the polishing pad according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] A polishing pad and a polishing apparatus according to an embodiment of the present invention will be described below. Fig. 1 is a schematic diagram of the polishing pad according to this embodiment, Fig. 2 is an enlarged view of a part of Fig. 1, and Fig. 3 is an enlarged view of the vicinity of the hollow particles in Fig. 2. Fig. 4 is a schematic diagram of the polishing apparatus equipped with the polishing pad according to this embodiment.

[0016] <<<Polishing pads>>> 1, polishing pad 10 is, for example, disc-shaped and includes polishing layer 11, cushion layer 12, and adhesive layer 13 for adhering polishing layer 11 and cushion layer 12. Polishing pad 10 includes cushion layer 12 and adhesive layer 13, but it is sufficient to include polishing layer 11, and it is not necessary to include cushion layer 12 and adhesive layer 13. Surface 10A of polishing pad 10 is surface 11A of polishing layer 11.

[0017] <<Polishing layer>> 2, the polishing layer 11 contains a resin 111 and hollow particles 112 dispersed in the resin 111. The thickness of the polishing layer 11 can be about 1 to 5 mm.

[0018] The density of the polishing layer 11 is not particularly limited, but is preferably 0.60 g / cm 3 More than 1.25g / cm 3 If the density is within the above range, the occurrence of scratches due to polishing by-products (polishing debris) can be reduced. The lower limit of the density of the polishing layer 11 is 0.65 g / cm 3 or more than 0.70g / cm 3 More preferably, the upper limit is 1.15 g / cm 3 or less than 1.10g / cm 3 The following is more preferable: The density of the polishing layer 11 can be measured according to the procedures and conditions described in the section <Measurement of Density of Polishing Layer> in the Examples below.

[0019] The Shore D hardness of the polishing layer 11 is not particularly limited, but is preferably 35 or more and 75 or less. If the Shore D hardness is 35 or more, minor irregularities can be flattened, and if the Shore D hardness is 75 or less, the occurrence of scratches on the polished object can be reduced. The lower limit of the Shore D hardness of the polishing layer 11 is more preferably 40 or more, or 45 or more, and the upper limit is more preferably 70 or less, or 65 or less. The Shore D hardness of the polishing layer 11 can be measured based on the procedure and conditions described in the <Shore D hardness measurement of the polishing layer> section of the Examples described later.

[0020] The polishing layer 11 has holes 11B formed by the hollow particles 112 opening on the surface 11A of the polishing layer 11. The average opening diameter of the holes 11B of the polishing layer 11 is preferably 1 μm or more and 20 μm or less. If the average opening diameter of the holes 11B of the polishing layer 11 is 1 μm or more, a large amount of slurry can be held near the surface 11A of the polishing layer 11 when the polishing object is polished. In addition, the polishing pad is scraped during polishing of the polishing object, and polishing debris is generated. However, if the average opening diameter is 20 μm or less, the polishing debris does not accumulate in the holes 11B of the polishing layer 11, and the occurrence of scratches can be further reduced. The lower limit of the average opening diameter of the holes 11B of the polishing layer 11 is more preferably 2 μm or more, 3 μm or more, or 4 μm or more, and the upper limit is more preferably 18 μm or less, 15 μm or less, or 10 μm or less. The average pore size can be measured using a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation).

[0021] <Resin> The resin 111 is not particularly limited, but is preferably, for example, a polyurethane resin. The polyurethane resin can be synthesized from a polyisocyanate and a polyol, and is particularly preferably a reaction product of a urethane prepolymer and a curing agent. The urethane prepolymer can be synthesized from a polyisocyanate and a polyol. The urethane prepolymer is preferably an isocyanate-terminated urethane prepolymer having an isocyanate group at the end. The structural units derived from the polyisocyanate and the polyol that constitute the polyurethane resin, and the curing agent will be described below.

[0022] (Structural unit derived from polyisocyanate) The polyisocyanate-derived structural unit is not particularly limited, and examples thereof include alicyclic isocyanate-derived structural units, aliphatic isocyanate-derived structural units, and aromatic isocyanate-derived structural units. Among these, aromatic isocyanate-derived structural units are preferred, and 2,4-tolylene diisocyanate (2,4-TDI)-derived structural units are more preferred.

[0023] The alicyclic isocyanate is not particularly limited, but examples thereof include 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, and isophorone diisocyanate.

[0024] The aliphatic isocyanate is not particularly limited, but examples thereof include hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), tetramethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, trimethylene diisocyanate, and trimethylhexamethylene diisocyanate.

[0025] The aromatic isocyanate is not particularly limited, but examples thereof include phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), xylylene diisocyanate, naphthalene diisocyanate, and diphenylmethane-4,4'-diisocyanate (MDI).

[0026] (Structural unit derived from polyol) The structural unit derived from a polyol is not particularly limited, and examples thereof include a low molecular weight polyol having a number average molecular weight of less than 300 and a high molecular weight polyol having a number average molecular weight of at least 300. Among these, it is preferable to use at least a low molecular weight polyol, and it is preferable to use a low molecular weight polyol and a high molecular weight polyol in combination.

[0027] The number average molecular weights of the low molecular weight polyol and the high molecular weight polyol can be measured as polyethylene glycol / polyethylene oxide (PEG / PEO) molecular weights based on gel permeation chromatography (GPC) under the following conditions. <Measurement conditions> Column: Ohpak SB-802.5HQ (exclusion limit 10000) + SB-803HQ (exclusion limit 100000) Mobile phase: 5mM LiBr / DMF Flow rate: 0.3ml / min (26kg / cm 2 ) Oven: 60℃ Detector: RI 40℃ Sample size: 20μ

[0028] The low molecular weight polyol is not particularly limited, but examples thereof include low molecular weight polyols having two hydroxyl groups such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexane glycol, 2,5-hexanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, tricyclodecane dimethanol, and 1,4-cyclohexane dimethanol; and low molecular weight polyols having three or more hydroxyl groups such as glycerin, hexanetriol, trimethylolpropane, isocyanuric acid, and erythritol. The low molecular weight polyol may be used alone or in combination of two or more. Among these, the low molecular weight polyol is preferably a low molecular weight polyol having two hydroxyl groups, and more preferably diethylene glycol.

[0029] The polymer polyol is not particularly limited, but may be, for example, polyether polyol, polyester polyol, polycarbonate polyol, polyether polycarbonate polyol, polyurethane polyol, epoxy polyol, vegetable oil polyol, polyolefin polyol, acrylic polyol, and vinyl monomer modified polyol. The polymer polyol may be used alone or in combination of two or more. Among these, the polymer polyol is preferably polyether polyol, and more preferably polytetramethylene ether glycol.

[0030] The number average molecular weight of the polymer polyol is preferably 300-3,000, more preferably 500-2,500, and most preferably 850-2,000.

[0031] (hardening agent) The curing agent is not particularly limited, but may be, for example, a polyamine. The curing agent may be used alone or in combination of two or more kinds.

[0032] The polyamine is not particularly limited, but examples thereof include aliphatic polyamines such as ethylenediamine, propylenediamine, and hexamethylenediamine; alicyclic polyamines such as isophoronediamine and dicyclohexylmethane-4,4'-diamine; and aromatic polyamines such as 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. In addition, trifunctional triamine compounds and polyamine compounds having 4 or more functional groups can also be used. Among these, aromatic polyamines are preferred, and it is more preferred to use 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA).

[0033] <Hollow particles> The hollow particles 112 are particles having a cavity inside. The shape of the hollow particles 112 is not particularly limited, but may be, for example, spherical or approximately spherical.

[0034] The hollow particle 112 has an outer shell 113 and a void 114 within the outer shell 113. The hollow particle 112 has one or more protrusions 112C on the inner surface 112A (the inner surface of the outer shell 113) of the hollow particle 112. One or more protrusions 112C may be present per hollow particle 112, but it is preferable that two or more protrusions 112C are present per hollow particle 112. When the hollow particle 112 has two or more protrusions 112C, the slurry that has entered the hollow particle 112 can flow more non-uniformly during polishing of the workpiece, and therefore deposition and aggregation of abrasive grain components in the slurry within the hollow particle 112 can be further suppressed.

[0035] The hollow particles having convex portions on the inner surface as described above can be prepared, for example, by suspension polymerization. The suspension polymerization can be carried out by a conventional method, for example, by suspending a mixture containing a polymer, a volatile compound, a polymerization initiator, a dispersant, and an aqueous medium, which is the material for the shell of the hollow particles, and polymerizing the suspension. The height and number of convex portions on the inner surface of the hollow particles can be adjusted by adjusting the compounding ratio of each component in the mixture and the removal rate of the volatile compound.

[0036] The porosity of the hollow particles 112 is preferably 20% or more and 60% or less. If the porosity of the hollow particles 112 is 20% or more, more slurry can be held in the hollow particles 112 when polishing the workpiece, and if the porosity is 60% or less, the slurry that has entered the hollow particles is more likely to flow non-uniformly when polishing the workpiece, so that deposition and aggregation of the abrasive grain components in the slurry in the hollow particles 112 can be more suppressed. The lower limit of the porosity of the hollow particles 112 is more preferably 25% or more, or 30% or more, and the upper limit is more preferably 55% or less, or 50% or less. The porosity of the hollow particles 112 can be determined by the apparent density and true density of the hollow particles 112.

[0037] The ratio of the height of the convex portion 112C in the hole 11B to the average opening diameter of the hole 11B of the polishing layer 11 (height of the convex portion 112C / average opening diameter of the hole 11B) is preferably 0.01 or more. If this ratio is 0.01 or more, the height of the convex portion 112C is not too small relative to the hole 11B, so that the slurry that has entered the hollow particle can flow more non-uniformly when polishing the object to be polished, and the deposition and aggregation of the abrasive grain components in the slurry in the hollow particle can be more suppressed. The lower limit of this ratio is more preferably 0.05 or more, or 0.1 or more, and the upper limit is more preferably 0.5 or less, or 0.2 or less, from the viewpoint of retaining more slurry in the hollow particle 112. The height of the convex portion can be measured by a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.).

[0038] The height of the protrusions 112C is preferably 0.1 μm or more. If this height is 0.1 μm or more, the height of the protrusions 112C is not too small, so that the slurry that has entered the hollow particles 112 can flow more non-uniformly when polishing the object to be polished, and deposition and aggregation of the abrasive grain components in the slurry within the hollow particles 112 can be further suppressed. The lower limit of this height is more preferably 0.3 μm or more, or 0.5 μm or more, and the upper limit is more preferably 5 μm or less, or 3 μm or less, from the viewpoint of retaining more slurry within the hollow particles 112.

[0039] The arithmetic mean roughness of the inner surface 112A of the hollow particle 112 is preferably 0.1 μm or more. If the arithmetic mean roughness is 0.1 μm or more, the height of the convex portion 112C is not too small, so that the slurry that has entered the hollow particle 112 can flow more non-uniformly when polishing the object to be polished, and deposition and aggregation of the abrasive grain components in the slurry in the hollow particle 112 can be more suppressed. The lower limit of the arithmetic mean roughness is more preferably 0.15 μm or more, or 0.2 μm or more, and the upper limit is more preferably 2 μm or less, or 1 μm or less, from the viewpoint of retaining more slurry in the hollow particle 112. The arithmetic mean roughness can be measured by an atomic force microscope (AFM).

[0040] When two or more convex portions 112C exist per hollow particle 112, the gap D between the convex portions 112C is preferably 5 μm or less as shown in FIG. 3. If the gap D is 5 μm or less, even if the abrasive grain components enter the gap and form aggregates during polishing of the object to be polished, the size of the aggregates will be small, so that the formation of coarse aggregates can be suppressed. As a result, even if the aggregates are exposed on the surface, the occurrence of scratches can be further reduced. In this specification, the "gap between convex portions" means the distance between the top of a convex portion and the top of a convex portion adjacent to this convex portion. It is more preferable that the gap between the convex portions 112C is 3.5 μm or less, or 1 μm or less. In addition, the lower limit of the gap between the convex portions 112C may be 0 μm or more, and is preferably 0.1 μm or more.

[0041] Hollow particle 112 particle diameter (D 50 It is preferable that the particle diameter (D 50 If the diameter (D) of the hollow particles 112 is 1 μm or more, a large amount of slurry can be held near the surface of the polishing layer 11 when the workpiece is polished. 50 If the diameter (D) of the hollow particles 112 is 20 μm or less, polishing waste will not accumulate in the holes of the polishing layer 11, and the occurrence of scratches can be further reduced.50 The lower limit of the particle diameter (D) of the hollow particles may be 2 μm or more, 3 μm or more, or 4 μm or more, and the upper limit of the particle diameter (D) of the hollow particles may be 18 μm or less, 15 μm or less, or 10 μm or less. 50 ) is also called the median diameter, and refers to the particle diameter at which the hollow particles are integrated from the smallest side to reach 50% volume in the cumulative particle size distribution obtained by measuring on a volume basis. 50 ) can be measured using a laser diffraction particle size distribution measuring device (for example, product name "Mastersizer 2000" manufactured by Spectris Co., Ltd.).

[0042] The material for the shell 113 of the hollow particle 112 is not particularly limited, but examples thereof include polyvinyl alcohol-based polymers, polyvinylpyrrolidone-based polymers, poly(meth)acrylic acid-based polymers, polystyrene-based polymers, polyacrylamide-based polymers, polyethylene glycol-based polymers, polyhydroxyether acrylate-based polymers, maleic acid copolymer-based polymers, polyethylene oxide-based polymers, polyurethane-based polymers, acrylonitrile-based polymers, and polyvinylidene chloride-acrylonitrile copolymer-based polymers.

[0043] The content of hollow particles 112 in the polishing layer 11 is preferably 0.1% by mass or more and 30% by mass or less. If the content of hollow particles 112 is 0.1% by mass or more, a large amount of slurry can be held near the surface of the polishing layer 11 when polishing the workpiece, and if the content is 30% by mass or less, the hollow particles 112 are uniformly dispersed without agglomeration. The lower limit of the content is more preferably 0.5% by mass or more, 2.0% by mass or more, or 4.0% by mass or more, and the upper limit is more preferably 25% by mass or less, 20% by mass or less, or 15% by mass or less.

[0044] The polishing pad 10 is used to polish an object to be polished. The object to be polished is not particularly limited, but examples thereof include optical materials, semiconductor wafers, and glass substrates for hard disks.

[0045] <<Polishing pad manufacturing method>> Such a polishing pad 10 can be manufactured, for example, as follows. First, a prepolymer such as a urethane prepolymer, a curing agent, and non-expandable hollow particles 112 having one or more convex portions 112C on the inner surface 112A are prepared. If expandable hollow particles are used as the hollow particles 112, the outer shell of the hollow particles becomes thin when heated and expanded, so that even if there are convex portions on the inner surface of the outer shell in an unexpanded state, the convex portions become smaller due to expansion. For this reason, it is preferable to use non-expandable hollow particles to form hollow particles having the above-mentioned convex portions in the polishing layer.

[0046] Next, the prepolymer and hollow particles 112 are mixed and kept at a temperature of 50° C. to 80° C. Meanwhile, the curing agent is kept at about 120° C. Note that the hollow particles 112 are non-expandable and do not expand when heated, so they may be added to the curing agent side, which has a higher temperature.

[0047] Thereafter, the prepolymer and hollow particles 112 are mixed with a curing agent to obtain a curable composition for the polishing layer. The curable composition for the polishing layer is then supplied to a mold and heated within a range of 75° C. to 140° C. to cure the curable composition for the polishing layer. This produces a block containing resin 111, which is a cured product of the curable composition for the polishing layer, and hollow particles 112.

[0048] The hardened block is removed from the mold and sliced ​​to a predetermined thickness to obtain the polishing layer 11. After grooves are formed on the surface of the polishing layer 11, it is bonded to the cushion layer 12 via the adhesive layer 13. Finally, it is cut into a disk shape. This produces the polishing pad 10.

[0049] The present inventors have intensively studied coarse abrasive grain components and found that coarse abrasive grain components are easily formed when the inner surface of the hollow particle is smooth. This is believed to be because when the inner surface of the hollow particle is smooth, the abrasive grain components in the slurry are easily deposited at a specific location (for example, the bottom) of the hollow particle. According to this embodiment, the hollow particle 112 has one or more convex parts 112C on the inner surface 112A of the hollow particle 112, so that during polishing, the slurry that has entered the hollow particle 112 flows non-uniformly due to the presence of the convex parts 112C, and the abrasive grain components also easily flow. As a result, the abrasive grain components in the slurry are less likely to deposit at a specific location, and therefore are less likely to aggregate. As a result, the formation of coarse abrasive grain components in the hollow particle 112 can be suppressed, and scratches caused by the coarse abrasive grain components can be reduced.

[0050] <<<Polishing equipment>>> The polishing pad is incorporated in a polishing apparatus for use. The polishing apparatus 20 shown in FIG. 4 is a chemical mechanical polishing apparatus. The polishing apparatus 20 includes a polishing pad 10, a polishing platen 21 to which the polishing pad 10 is attached by a double-sided tape (not shown) or the like provided on the cushion layer 12 of the polishing pad 10, a holding platen 22 for holding the object 30 to be polished, and a slurry supplying unit 23 for supplying a slurry containing an abrasive component when polishing the object 30 to be polished. The polishing pad 10 rotates together with the polishing platen 21 with the object 30 to be polished pressed against the surface 10A of the polishing pad 10, and polishes the object 30 to be polished. At that time, a slurry is supplied from the slurry supplying unit 23 between the polishing pad 10 and the object to be polished. The slurry is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive components, and the polishing effect is increased by the relative movement with the object 30 to be polished while the chemical components and abrasive components in the slurry are flowing. The slurry is supplied to the polishing surface through grooves (not shown) or holes 11B provided in the polishing layer 11 and is discharged therefrom. EXAMPLES

[0051] In order to explain the present invention in detail, the following examples are given, but the present invention is not limited to these. Fig. 5 is an SEM image of the cross section of the polishing layer of the polishing pad of Example 1 at a magnification of 10,000 times, and Fig. 6 is an SEM image of the cross section of the polishing layer of the polishing pad of Comparative Example 1 at a magnification of 1,000 times.

[0052] <Example 1> First, an isocyanate-terminated urethane prepolymer (1), an isocyanate-terminated urethane prepolymer (2), a curing agent, and non-expanding hollow particles (1) (trade name "Techpolymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.) were prepared. The isocyanate-terminated urethane prepolymer (1) was obtained by reacting 2,4-tolylene diisocyanate (2,4-TDI), polypropylene glycol (PPG1000) having a number average molecular weight of 1000, and diethylene glycol (DEG), and had an NCO equivalent of 560. The isocyanate-terminated urethane prepolymer (2) was obtained by reacting 2,4-tolylene diisocyanate (2,4-TDI), butylene glycol adipate ester having a number average molecular weight of 2000, and diethylene glycol (DEG), and had an NCO equivalent of 600. As a curing agent, 4,4-methylenebis(2-chloroaniline) (MOCA) was prepared. The hollow particles (1), Techpolymer (registered trademark), had a particle size (D 50 ) is 6 μm, and the particles have protrusions on their inner surfaces.

[0053] Next, the isocyanate group-terminated urethane prepolymer (1) and the isocyanate group-terminated urethane prepolymer (2) were mixed in a mass ratio of 1:1, and the hollow particles (1) were mixed, heated to 65°C, and degassed under reduced pressure. The curing agent MOCA was dissolved at 120°C and degassed under reduced pressure. Then, the mixed isocyanate group-terminated urethane prepolymer and hollow particles (1) were mixed with the curing agent so that the content of the hollow particles (1) was 5% by mass relative to 100 parts by mass of the isocyanate-terminated urethane prepolymer. The resulting mixture was poured into a mold and primarily cured at 80°C for 30 minutes. The formed block containing the urethane resin and hollow particles was removed from the mold and secondary cured in an oven at 120°C for 4 hours. The resulting block was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours. The obtained block was sliced ​​in a direction perpendicular to the thickness direction of the block to prepare an abrasive layer having a thickness of 1.3 mm, and a double-sided tape was attached to the back surface of this abrasive layer to prepare a polishing pad.

[0054] <Example 2> In Example 2, a polishing pad was obtained in the same manner as in Example 1, except that the content of hollow particles (1) was 10 mass %.

[0055] <Example 3> In Example 3, a polishing pad was obtained in the same manner as in Example 1, except that non-expanding hollow particles (2) (trade name "Techpolymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.) different from the hollow particles (1) were used instead of the hollow particles (1) and the content of the hollow particles (2) was set to 3 mass %. The Techpolymer (registered trademark) hollow particles (2) had a particle diameter (D 50 ) is 13 μm, and the particles have protrusions on their inner surfaces.

[0056] <Comparative Example 1> In Comparative Example 1, a polishing pad was obtained in the same manner as in Example 1, except that hollow particles (3) (product number "Expancel (registered trademark) 461DU20", manufactured by Nippon Fillite Co., Ltd.) having a different expandability from hollow particles (1) was used instead of hollow particles (1) and the content of hollow particles (3) was set to 3 mass %. Expancel (registered trademark) 461DU20, which is hollow particles (3), has a particle diameter (D 50 ) is 6 to 8 μm before expansion, and has no protrusions on the inner surface of the particle.

[0057] <Comparative Example 2> In Comparative Example 2, a polishing pad was obtained in the same manner as in Comparative Example 1, except that the content of hollow particles (3) was 5 mass %.

[0058] <Comparative Example 3> In Comparative Example 3, a polishing pad was obtained in the same manner as in Example 1, except that non-expandable hollow particles (4) (product number "Techpolymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.) different from the hollow particles (1) were used instead of the hollow particles (1). 50 ) was 6 μm and had no protrusions on the inner surface of the particle.

[0059] Table 1 shows the formulations of the curable compositions for the polishing layer used in Examples 1 to 3 and Comparative Examples 1 to 3. [Table 1] In Table 1, PP means an isocyanate group-terminated urethane prepolymer.

[0060] <Checking for protrusions inside hollow particles> In the polishing pads according to Examples 1 and 2 and Comparative Example 3, a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.) was used to observe the cross section of the polishing layer at a magnification of 10,000 times to confirm whether or not there are convex portions on the inner surface of the hollow particles. In addition, in the polishing pads according to Example 3 and Comparative Examples 1 and 2, a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.) was used to observe the cross section of the polishing layer at a magnification of 1000 times to confirm whether or not there are convex portions on the inner surface of the hollow particles. The magnification for observing the cross section of the polishing pads according to Example 3 and Comparative Examples 1 and 2 was lower than that for observing the cross section of the polishing pads according to Examples 1, 2 and Comparative Example 3 because the hollow particles used in the polishing pads according to Example 3 and Comparative Examples 1 and 2 were larger than the hollow particles used in the polishing pads according to Examples 1, 2 and Comparative Example 3, making observation at a magnification of 10,000 times difficult.

[0061] <Porosity measurement of hollow particles> The porosity of the hollow particles was determined for the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, the apparent density (g / cm 3 ) and true density (g / cm 3 ) was measured, and the porosity of the hollow particles was calculated based on the following formula (1). Porosity (%) = 100 - (apparent density / true density) x 100 ... Formula (1)

[0062] The apparent density of the hollow particles was measured as follows. 3 About 30 cm 3 The hollow particles were filled in the measuring flask, and the mass of the filled hollow particles was weighed. Next, the measuring flask filled with the hollow particles was filled with isopropanol up to the marked line, taking care not to introduce air bubbles. The mass of the isopropanol added to the measuring flask was weighed, and the apparent density (g / cm) of the hollow particles was calculated based on the following formula (2). 3 ) was calculated. Apparent density = [mass of hollow particles] / (100 - [mass of isopropanol] ÷ [specific gravity of isopropanol at measurement temperature]) ... Equation (2)

[0063] The true density of the hollow particles was measured as follows. First, the hollow particles were crushed in advance and then crushed into a 100 cm 3 The measuring flask was filled with about 10 g of crushed pieces of hollow particles, and the mass of the crushed pieces was weighed. Next, isopropanol was added to the measuring flask in the same manner as in the measurement of the apparent density described above, and the mass of the isopropanol was weighed, and the true density (g / cm3) of the hollow particles was calculated based on the following formula (3). True density = [mass of crushed pieces of hollow particles] / (100 - [mass of isopropanol] ÷ [specific gravity of isopropanol at the measurement temperature]) ... Equation (3)

[0064] <Calculation of the ratio of the height of the convex portion of the hollow particle to the average opening diameter of the pores of the polishing layer> In the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3, the average opening diameter of the holes in the polishing layer and the height of the protrusions in the hollow particles constituting the holes were measured, and the ratio of the height of the protrusions of the hollow particles to the average opening diameter of the holes in the polishing layer was calculated. Specifically, three areas (each a rectangle of 0.5 mm long x 0.7 mm wide) were arbitrarily selected from the surface of the polishing layer without bias, and each area was observed at 10,000 times magnification using a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.). In each of the obtained images, the hollow particles were confirmed, and the height of each protrusion present in the hollow particles was manually measured. Then, the height of each obtained protrusion was averaged to calculate the height of the protrusions in the hollow particles. The calculated protrusion height was divided by the average opening diameter of the holes in the polishing layer calculated by the method described later, to calculate the ratio of the height of the protrusions of the hollow particles to the average opening diameter of the holes in the polishing layer. Three holes were used for the measurement, and the ratio of the height of the convex portion of the hollow particle to the average opening diameter of the holes in the polishing layer was taken as the average value.

[0065] <Measurement of gaps between protrusions of hollow particles> In the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3, when two or more convex portions exist in a hollow particle, the gap between the convex portions was measured. Specifically, three regions (each a rectangle of 0.5 mm long x 0.7 mm wide) were arbitrarily selected from the surface of the polishing layer without bias, and each region was observed at 10,000 times magnification using a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.). In each of the obtained images, the hollow particles were confirmed, and each gap between the convex portions present in the hollow particles was manually measured. Then, the obtained gaps between the convex portions were averaged to calculate the gap between the convex portions in the hollow particles. The number of hollow particles used in the measurement was three, and the gap between the convex portions of the hollow particles was the average value of the three.

[0066] <Measurement of the arithmetic mean roughness of the inner surface of hollow particles> The arithmetic mean roughness of the inner surface of the hollow particles was measured for the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, a sample piece measuring 1 cm x 1 cm was first taken from each polishing layer. Then, air was blown onto the sample piece to remove dust and other particles adhering to the surface of the sample piece. After that, the sample piece was set in an atomic force microscope (product name "Park NX10", manufactured by Park Systems), and the height of the cantilever (product name "OMCL-AC160TS", manufactured by Olympus Corporation) was adjusted. Detailed information on the cantilever is described below. (Cantilever) Shape: rectangular Length: 160μm ·Resonance frequency: 300kHz Spring constant: 26N / m Material: Silicone ·Tip shape: square pyramid ·Tip height: 14μm ·Tip tip curvature: 7nm Probe material: Silicon Next, the positions of the open hollow particles present on the surface of the sample piece were roughly grasped using an atomic force microscope. Then, the atomic force microscope was aimed at the inside of the hollow particles, and the arithmetic mean roughness was measured. The measurement area was 4 μm × 4 μm. The number of hollow particles used in the measurement was three, and the arithmetic mean roughness was the average value of the three.

[0067] <Measurement of density of polishing layer> The density was measured for the polishing layers of the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, the measurement was performed in accordance with the Japanese Industrial Standard (JIS K 6505:1995).

[0068] <Shore D hardness measurement of polishing layer> The Shore D hardness was measured for the polishing layers of the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, the Shore D hardness was measured using a D-type hardness tester in accordance with the Japanese Industrial Standards (JIS K 6253-1 and 6253-3:2012). Here, the measurement sample was obtained by stacking multiple polishing layers as necessary so that the total thickness was at least 4.5 mm or more.

[0069] <Measurement of average pore diameter> The pore diameter of the holes in the polishing layer of the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3 was measured to obtain the average pore diameter. Specifically, three areas (each a rectangle of 0.5 mm long x 0.7 mm wide) were selected from the surface of the polishing layer without bias, and each area was observed at 400 times magnification using a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation). Each image obtained (rectangle of 0.5 mm long x 0.7 mm wide) was binarized using image processing software (software name "WinROOF2018 Ver4.0.2", manufactured by Mitani Shoji Co., Ltd.) to confirm the pores, and the circle equivalent diameter (pore diameter) was calculated from the area of ​​each pore. The cutoff value (lower limit) of the pore diameter was set to 1 μm, and noise components were excluded. Then, all the pore diameters contained in each of the above areas (images) were averaged to calculate the average pore diameter of each area. The average pore diameters of the three regions thus obtained were then averaged to calculate the final average pore diameter.

[0070] <Polishing test> Using the polishing pads of Examples 1 to 3 and Comparative Examples 1 to 3, polishing tests were carried out under the following polishing conditions.

[0071] (polishing conditions) Polishing machine used: F-REX300X (manufactured by Ebara Corporation) Disk:34J (KINIK) Abrasive temperature: 20℃ Polishing platen rotation speed: 85 rpm Polishing head rotation speed: 86 rpm Grinding pressure: 1.18psi Polishing slurry (metal film): CSL-9044C (CSL-9044C stock solution: pure water = mixed solution of 1:9 by weight) (manufactured by Fujimi Corporation) Polishing slurry flow rate: 200ml / min Polishing time: 60 seconds Polished object (metal film): Cu film substrate (disc-shaped, 300 mm in diameter) Pad break: 32N, 10 minutes Conditioning: Ex-situ, 32N, 4 scans

[0072] (Scratch evaluation) Using the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3, four Cu film substrates were polished under the above-mentioned polishing conditions, and defects (surface defects) with a size of 110 nm or more were detected on the entire Cu film substrate after polishing using a high sensitivity measurement mode of a wafer surface inspection device (product name "Surfscan SP5", manufactured by KLA Tencor Corporation). For each detected defect, an SEM image taken using a review SEM was analyzed, and the defects were classified into "particles," "pad debris," and "scratches," and the number of scratches among them was counted. The result was the average value of the results obtained by polishing four Cu film substrates. The classification "particles" means fine particles remaining on the surface of the substrate, the classification "pad debris" means debris of the polishing layer attached to the surface of the substrate, and the classification "scratches" means scratches on the surface of the substrate. The evaluation criteria were as follows. A: There were significantly fewer scratches. B: A few scratches were observed, but were not of a level that would cause any practical problems. C: There were a few scratches. D: There were significantly more scratches.

[0073] (polishing rate) Using the polishing pads according to Examples 1 to 3 and Comparative Examples 1 to 3, the polishing rate (Å / min) of the polished substrate was measured under the above-mentioned polishing conditions as follows. First, the Cu film substrate before and after the polishing test was measured in the diameter direction on the Cu film substrate, and the thickness at those points before and after the polishing test was measured. Then, based on the measured thickness, the average thickness before the polishing test and the average thickness after the polishing test were calculated, and the average polished thickness was calculated by calculating the difference between these average values. Then, the polishing rate was calculated by dividing the obtained average polished thickness by the polishing time. The thickness was measured using a four-probe sheet resistance measuring device (product name "RS-200", manufactured by KLA Tencor Corporation, measurement: DBS mode). The evaluation criteria were as follows. A: The removal rate was very high. B: The polishing rate was high. C: The removal rate was slightly low. D: The removal rate was very low.

[0074] The results are shown in Table 2. [Table 2]

[0075] First, as shown in FIG. 5, the hollow particles contained in the polishing layer of the polishing pad according to Example 1 had a convex portion on the inner surface. Similarly, the hollow particles contained in the polishing layer of the polishing pad according to Examples 2 and 3 also had a convex portion on the inner surface. In contrast, as shown in FIG. 6, the hollow particles contained in the polishing layer of the polishing pad according to Comparative Example 1 had a smooth inner surface and did not have a convex portion. Similarly, the hollow particles contained in the polishing layer of the polishing pad according to Comparative Examples 2 and 3 also had a smooth inner surface and did not have a convex portion.

[0076] As shown in Table 2, the polishing pads according to Comparative Examples 1 to 3 had many scratches and a low polishing rate because the hollow particles dispersed in the polishing layer did not have convex parts on the inner surface. In contrast, the polishing pads according to Examples 1 to 3 had hollow particles dispersed in the polishing layer with convex parts on the inner surface, so scratches were reduced and the polishing rate was high. Therefore, it was confirmed that the occurrence of scratches can be reduced by having convex parts on the inner surface of the hollow particles. [Explanation of symbols]

[0077] 10...Polishing pad 11...polishing layer 11A…Surface 11B…hole 12…Cushion layer 20...polishing device 111…Resin 112...Hollow particle 112A…Inner surface 112B…Outer surface 112C…Convex part

Claims

1. A polishing pad comprising a polishing layer, the polishing layer includes a resin and hollow particles dispersed in the resin; The polishing pad, wherein the hollow particles have one or more protrusions on the inner surface of the hollow particles.

2. 2. The polishing pad according to claim 1, wherein the porosity of the hollow particles is 20% or more and 60% or less.

3. 2. The polishing pad according to claim 1, wherein the polishing layer has holes formed by openings of the hollow particles on the surface of the polishing layer, and the ratio of the height of the convex portion within the hole to the average opening diameter of the hole is 0.01 or more.

4. 2. The polishing pad according to claim 1, wherein two or more of the convex portions are present for one of the hollow particles, and a gap between the convex portions is 5 μm or less.

5. 2. The polishing pad according to claim 1, wherein the arithmetic mean roughness of the inner surface of the hollow particles is 0.1 μm or more.

6. A polishing apparatus comprising the polishing pad according to claim 1 .

Citation Information

Patent Citations

  • Production of microporous molded product and urethane resin composition for producing the same

    JP1999322877A

  • Method for manufacturing polyurethane foam and method for manufacturing polishing pad

    JP2010274362A

Cited By

  • LASER DEVICE

    DE102026112341A1